Risk, science, and politics : regulating toxic substances in Canada and the United States - Harrison, Kathryn, 1958- (McGill-Queen's University Press, 1994)
"Government regulation of toxic substances varies dramatically between the United States and Canada. In Risk, Science, and Politics Kathryn Harrison and George Hoberg analyse these differences and evaluate the strengths and weaknesses of two very different regulatory styles." "The Canadian approach is exemplified by closed decision making, case-by-case review that relies heavily on expert judgement, and limited public debate about the scientific basis of regulatory decisions. In contrast, regulatory science in the United States is characterized by publication of lengthy rationales for regulatory decisions, reliance on standardized procedures for risk assessment, and controversy surrounding the interpretation of scientific evidence. Harrison and Hoberg's detailed comparisons will help readers understand the complexities and subtleties involved in regulation of toxic substances."--Jacket